TRPV1 Channels Regulate Cortical Excitability in Humans - Mori, Francesco; Ribolsi, Michele; Kusayanagi, Hajime; Monteleone, Fabrizia; Mantovani, Vilma; Buttari, Fabio; Marasco, Elena; Bernardi, Giorgio; Maccarrone, Mauro; Centonze, Diego (The Journal of neuroscience, 2012)
Studies in rodents show that transient receptor potential vanilloid 1 (TRPV1) channels regulate glutamate release at central and peripheral synapses. In humans, a number of nonsynonymous single-nucleotide polymorphisms (SNPs) have been described in the TRPV1 gene, and some of them significantly alter the functionality of the channel. To address the possible role of TRPV1 channels in the regulation of synaptic transmission in humans, we studied how TRPV1 genetic polymorphisms affect cortical excitability measured with transcranial magnetic stimulation (TMS). Two SNPs of the TRPV1 gene were selected and genotyped (rs222747 and rs222749) in a sample of 77 healthy subjects. In previous cell expression studies, the “G” allele of rs222747 was found to enhance the activity of the channel, whereas rs222749 had no functional effect. Allelic variants in the rs222749 region were not associated with altered cortical response to single, paired, and repetitive TMS. In contrast, subjects homozygous for the G allele in rs222747 exhibited larger short-interval intracortical facilitation (a measure of glutamate transmission) explored through paired-pulse TMS of the primary motor cortex. Recruitment curves, short-interval intracortical inhibition, intracortical facilitation, and long-interval intracortical inhibition were unchanged. LTP- and LTD-like plasticity explored through intermittent or continuous theta-burst stimulation was also similar in the “G” and “non-G” subjects. To our knowledge, our results provide the first evidence that TRPV1 channels regulate cortical excitability to paired-pulse stimulation in humans.